Experimental and theoretical study of the (n,2n) reactions on 174,175Hf isotopes - Krokidi, K.; Vlastou, R.; Kalamara, A.; Serris, M.; Stamatopoulos, A.; Hassapoglou, S.; Michalopoulou, V.; Kokkoris, M.; Axiotis, M.; Lagoyannis, A. (HNPS Advances in Nuclear Physics, 2019)
N/A